2011
DOI: 10.1017/s0967199411000669
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the viability of embryos stored in liquid nitrogen produced commercially using culture medium as a complementary test for stereoscopic microscopy

Abstract: Summary The objective of the present study was to evaluate the viability of frozen embryos obtained from various private farmers in a culture medium for 4 h. Forty-seven embryos were used that had been previously graded as good and fair. These embryos were evaluated using stereoscopic microscopy by experienced clinicians prior to freezing. Embryos were divided in two groups: the non-cultured group, made up of six good quality embryos, and five fair; and the cultured group that consisted of 20 good quality embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…(2002) found that inaccuracies in evaluating the quality of Bos indicus embryos may be as high as 30%. This level of inaccuracy was confirmed in a comparison of transmission electron microscopy, phase contrast microscopy and stereoscopic microscopy for embryo assessment (Godinez et al., 2013; Godinez et al., 2012; Gutiérrez et al., 2014; López‐Damián et al., 2008). These findings may not be surprising since earlier studies, (Farin et al., 1995) in Bos taurus cattle showed that the accuracy of grading embryo quality by evaluators was only 68.5%.…”
Section: Issues Affecting Embryo Harvest and Qualitymentioning
confidence: 86%
“…(2002) found that inaccuracies in evaluating the quality of Bos indicus embryos may be as high as 30%. This level of inaccuracy was confirmed in a comparison of transmission electron microscopy, phase contrast microscopy and stereoscopic microscopy for embryo assessment (Godinez et al., 2013; Godinez et al., 2012; Gutiérrez et al., 2014; López‐Damián et al., 2008). These findings may not be surprising since earlier studies, (Farin et al., 1995) in Bos taurus cattle showed that the accuracy of grading embryo quality by evaluators was only 68.5%.…”
Section: Issues Affecting Embryo Harvest and Qualitymentioning
confidence: 86%
“…However, other factors have an important effect on the success of the technique. One such factor is the increasing evidence that Bos indicus embryos are structurally different from Bos taurus embryos [ 113 , 114 ]. Thus, the grading of an embryo as a suitable candidate for transfer can be erroneous [ 115 ].…”
Section: Breeding Proceduresmentioning
confidence: 99%